Balanced and sustainable economic development – the innovation collaboration in the Arctic - Longi, Henna; Niemelä, Sami (Oulun ammattikorkeakoulu, Oamk, 2019)
The Arctic and other peripheral regions are continuously challenged by the global mega trend of urbanization. The viability of these northern regions requires intentional actions and decisions. This paper presents a new approach, regional innovation systems, to meet the challenges as an alternative to existing Arctic economic policies resorting more on the exploitation of natural resources in the Arctic. This study is based on qualitative data (the interviews, the analysis of strategies, documents and reports) as well as the quantitative data of regional economic development. This article is based on the authors’ presentation in the Arctic Frontiers conference held in Tromsø, Norway 21.–24.1.2019.